Overview of Breastfeeding Under COVID-19 Pandemic - Pang, Zehan; Hu, Ruolan; Tian, Lili; Lou, Fuxing; Chen, Yangzhen; Wang, Shuqi; He, Shiting; Zhu, Shaozhou; An, Xiaoping; Song, Lihua; Liu, Feitong; Tong, Yigang; et al. (Frontiers in Immunology, 2022)
During the global pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), pregnant and lactating women are at higher risk of infection. The potential of viral intrauterine transmission and vertical transmission by breastfeeding has raised wide concerns. Breastmilk is rich in nutrients that contribute to infant growth and development, and reduce the incidence rate of infant illness and death, as well as inhibit pathogens significantly, and protect infants from infection. Although it is controversial whether mothers infected with COVID-19 should continue to breastfeed, many countries and international organizations have provided recommendations and guidance for breastfeeding. This review presents the risks and benefits of breastfeeding for mothers infected with COVID-19, and the reasons for the absence of SARS-CoV-2 active virus in human milk. In addition, the antiviral mechanisms of nutrients in breastmilk, the levels of SARS-CoV-2 specific antibodies in breastmilk from COVID-19 infected mothers and vaccinated mothers are also summarized and discussed, aiming to provide some support and recommendations for both lactating mothers and infants to better deal with the COVID-19 pandemic.